Regulatory problems and developmental psychopathology within the first 2 years of living—a nested in cohort population-based study - Ammitzbøll, Janni; Olsen, Anne Lise; Landorph, Susanne; Ritz, Christian; Skovgaard, Anne Mette (Frontiers in Child and Adolescent Psychiatry, 2024)
Background: Infancy regulatory problems (RP) of sleep, feeding and eating, and excessive crying are suggested to play a key role in the development of psychopathology in childhood, but knowledge is limited on the early trajectories. Objective: To explore RP at ages 8-11 months and the associations to mental health problems at ages 1½ years and assess the influences of maternal mental health problems and relationship problems. Methods: RP was explored in a nested in cohort sample (N=416) drawn from a community-based cohort (N=2,973). Cohort children were examined by community health nurses, using a mental health screening, which included seven items on RP. Follow-up at 1½ years included diagnostic assessment according to the International Classification of Diseases, ICD-10 and the Diagnostic Classification of Mental Health and Developmental disorders in Infancy and Early Childhood: Revised edition, DC:0-3R. Data analyses included logistic regression models and analyses of the mediation effect of maternal mental health and relationship problems. Results: RP of sleep were associated with a two-fold increased risk of child mental disorder specifically sleep disorders, adjusted OR 9.3 (95% CI 2.0-42.9), disorders of behavior and emotions, adjusted OR 2.9 (95% CI 1.0-8.4), and DC:0-3R regulatory disorders, adjusted OR 2.7 (95% CI 1.0-7.5). Children with RP of feeding and eating showed an increased risk of overall mental disorder, adjusted OR 1.4 (95% CI 0.7-2.4), and specifically, feeding and eating disorders, adjusted OR 6.0 (95% CI 1.6-21.7), disorders of behavior and emotions, adjusted OR 2.2 (95% CI 0.9-5.8), as well as DC:0-3R regulatory disorders, adjusted OR 1.6 (1.0-7.5). RP of emotional regulation were associated with increased risk of any mental disorder, adjusted OR 1.5 (1.0-2.4), and specifically behavioral and emotional disorders, adjusted OR 2.2 (95% CI 0.9-5.9) and DC:0-3R relationship disorders, adjusted OR 1.8 (95% CI 0.9-3.8). The mediation effect of maternal mental health problems and relationship problems ranged between 0 and 48%. Conclusion: RP at ages 8-11 months is associated with increased risk of ICD-10 and DC:0-3R disorders at 1½ years. Study findings highlight a group of vulnerable infants in need of preventive intervention to break the early trajectories of psychopathology.